THE EFFECT OF ENVIRONMENTAL TAX ON POLLUTION CONTROL IN NIGERIA - Tayo, A. G.; Oladipo, O. N. (Farabi Journal of Social Sciences, 2022)
The study examined effects of environmental taxes on pollution control in Nigeria. It especially evaluated the influence of environmental tax on waste disposal in Nigeria. The research predicated on planned behaviour theory and value belief norm theory of environmentalism. Primary data source was studied in presenting the facts of the situation. Purposive probability sampling methods was utilized to identify targeted respondents. Data gathered was examined using descriptive statistics for 100 surveys. The studies demonstrated that environmental tax has substantial influence on pollution reduction. This is based on the fact that a higher number (95 percent) of the respondents is in concord with the premise that environmental tax has considerable influence on pollution control. It was determined that environmental tax has beneficial and considerable influence on pollution control in Nigeria The researcher recommends that considering the seriousness of this environmental hazards which posed a great threat to the life of the people, It is the responsibility of the Federal Government of Nigeria to establish a tax system that would allow environmental tax policies, so that the levy of tax may be planned laying its weight on those who are responsible for generating a specific environmental issue, or problems, and also to make provision for statutory incentives to reduce the administrative cost to the government and the compliance cost placed on the tax payers. Keywords: environmental tax, waste disposal, planned behavior, tax compliance.